2020
DOI: 10.1039/c9se01044k
|View full text |Cite
|
Sign up to set email alerts
|

Optimized electrode structure for performance and mechanical stability in a direct formate fuel cell using cation ionomer

Abstract: In DFFC systems, there are different optimal points depending on the content of cation ionomer with regard to the cell performance and mechanical cell stability during the cell operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Furthermore, PdB Inc. /C shows a better concentration loss compared to Pd/ C. In a direct formate fuel cell system, fuel accessibility for the electrode is critical to alleviating the mass-transport limitation. 49 If the metallic states on the anode electrode are too high, such as that in Pd/C, 24 fuel accessibility might be hindered, even though its catalytic activity is improved. However, the lower metallic state of PdB Inc. /C, caused by B, could facilitate the fuel accessibility so that the concentration loss is alleviated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, PdB Inc. /C shows a better concentration loss compared to Pd/ C. In a direct formate fuel cell system, fuel accessibility for the electrode is critical to alleviating the mass-transport limitation. 49 If the metallic states on the anode electrode are too high, such as that in Pd/C, 24 fuel accessibility might be hindered, even though its catalytic activity is improved. However, the lower metallic state of PdB Inc. /C, caused by B, could facilitate the fuel accessibility so that the concentration loss is alleviated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…14,15 In the last few years, increasing attention has been focused on direct formate fuel cells (DFFCs). 16,17 DFFCs have indeed higher theoretical cell voltage (1.45 V with oxygen as the oxidant) with respect to other liquid fuel cells running on methanol (1.21 V) or ethanol (1.14 V). Moreover, formate can be easily stored and transported as a salt, thus minimizing hazards.…”
Section: Introductionmentioning
confidence: 93%
“…Pt has been selected as it is the benchmark catalyst for the oxygen reduction reaction (ORR) [38][39][40] and is commonly used in DFFCs. 16,17 To hold the pH difference between the cathode and the anode sides, the two half-cells were separated by a Naon® 115 membrane. A Naon® ionomer is generally employed as proton exchange membrane in acid media fuel cells, however it has also been applied as a cation exchange membrane in DFFCs to separate a basic anode from an acid cathode.…”
Section: Electrochemical Behaviourmentioning
confidence: 99%
“…Jervis et al showed that hydrogen oxidation reaction (HOR) under alkaline conditions with Nafion binder underestimated the catalytic activity due to the acidic ionomer binder acting as an insulator of hydroxide transport . Nonetheless, several groups have developed anion ionomer-free binders such as polytetrafluoroethylene (PTFE) and Nafion as a cation ionomer to transfer Na + in alkaline-acid fuel cells. Even though these DLFCs have high power densities, the use of two liquids and often the use of harmful oxidants make commercialization of these systems difficult. Thus, development of an effective AEI is imperative to further the advancement of conventional AEM fuel cells.…”
Section: Introductionmentioning
confidence: 99%